Preparation method of bimetallic mnco-zif nanoenzyme and application thereof in nitrite detection

CN122978459APending Publication Date: 2026-10-27QUFU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611191123.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

传统的单信号比色法易受外界环境因素(如温度、光照、背景颜色等)和操作人员主观判断的影响,检测准确性不佳

Benefits of technology

(1)本发明通过简单的溶剂热法制备得到MnCo-ZIF,制备方法简便,材料易于获得且制备的MnCo-ZIF纳米酶具有良好的水分散性及稳定性,表现出良好的类氧化酶活性。该发明能够催化3,3',5,5'-四甲基联苯胺(TMB)氧化,生成在652 nm处具有明显吸收峰的蓝色氧化产物(OXTMB)。在酸性条件下,亚硝酸盐能够与OXTMB发生重氮化反应及氧化反应,从而导致652 nm处吸光度降低,445 nm处吸光度上升,溶液颜色从蓝色变为绿色再变为黄色,利用A445/A652的比率变化,实现了对亚硝酸盐的定量检测。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978459A_ABST
    Figure CN122978459A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a bimetallic MnCo-ZIF nanoenzyme and application of the bimetallic MnCo-ZIF nanoenzyme in nitrite detection, and belongs to the technical field of nanoenzymes and colorimetric sensing. The bimetallic MnCo-ZIF nanoenzyme material is simply synthesized by using cobalt nitrate hexahydrate, manganese chloride tetrahydrate and 2-methylimidazole as raw materials and adopting a solvothermal method. The material has excellent water dispersibility, structural stability and oxidase-like catalytic activity, can catalyze the oxidation of a substrate TMB to generate a blue product, the absorbance of the system changes in a ratio at 445 nm and 652 nm after the addition of nitrite, quantitative detection of the nitrite is realized, the test paper strip can be prepared by loading the material on filter paper, and the instant detection of the nitrite can be realized by combining an intelligent mobile phone RGB analysis. The spiked recovery rates of actual water samples, meat products, pickled vegetables and the like are good, the detection accuracy is high, and the visual and sensitive detection of the nitrite is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanozyme and colorimetric sensing technology, specifically relating to a method for preparing a bimetallic MnCo-ZIF nanozyme and its application in nitrite detection. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Nitrite (NO2) - Nitrites are a common class of nitrogen-containing compounds widely used in food preservation and maintenance. However, excessive intake of nitrites may cause methemoglobinemia and, under certain conditions, can be converted into carcinogenic nitrosamines, posing a potential risk to human health. The World Health Organization stipulates that the permissible intake of nitrites in drinking water should not exceed 3 mg / L. Therefore, developing simple, rapid, and sensitive methods for detecting nitrites is of significant practical importance.

[0004] Currently, various methods for detecting nitrite have been reported, including high-performance liquid chromatography (HPLC), electrochemical methods, and fluorescence methods. However, these methods are often limited in practical applications by complex sample pretreatment, limited anti-interference capabilities, high equipment costs, and demanding operational requirements. In contrast, colorimetric methods, with their advantages of fast response, high sensitivity, low cost, and visual detection, have become a strong choice for nitrite detection. Traditional single-signal colorimetric methods are easily affected by external environmental factors (such as temperature, light, and background color) and operator subjective judgment, resulting in poor detection accuracy. Ratio colorimetric methods significantly reduce the impact of environmental interference on the measurement results by comparing the ratio of the optical intensities of two sets of signals. However, most existing ratio colorimetric systems use single metal nanozymes or require complex material modifications, and their colorimetric response efficiency and selectivity for nitrite still need improvement. Furthermore, the detection process relies on large instruments, making it difficult to meet the needs of rapid on-site detection.

[0005] Therefore, there is an urgent need to develop a new method that is easy to operate, has strong anti-interference capabilities, and can achieve rapid, visual, and quantitative detection to meet the practical needs of real-time on-site monitoring of nitrite in food. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a method for preparing bimetallic MnCo-ZIF nanozymes and their application in nitrite detection. The method is not only simple to synthesize, but also features high specificity, low cost, and visual detection capabilities, making it suitable for the specific detection of nitrite.

[0007] Nanozymes are nanomaterials with enzyme-like catalytic activity. Compared to natural enzymes, they typically exhibit higher catalytic activity, better stability, ease of synthesis, and reusability, thus finding wide application in fields such as biosensing, disease diagnosis and treatment, and environmental monitoring and remediation. Compared to single-metal nanozymes, bimetallic or mixed-metal nanozymes often exhibit synergistic effects, increasing the number of active sites, improving catalytic performance, and enhancing structural stability.

[0008] Zeolitic imidazolate frameworks (ZIFs) belong to a class of metal-organic frameworks (MOFs) and are assembled from metal ions and imidazolium and its derivatives through coordination bonds. ZIFs possess high specific surface area, significant porosity, good chemical and thermal stability, synergistic combination of inorganic and organic materials, and excellent structural tunability, thus showing broad application prospects in catalysis, sensing, separation and other fields.

[0009] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, this invention provides a method for preparing bimetallic MnCo-ZIF nanozymes, the method comprising the following steps: (1) Dissolve cobalt salt and manganese salt in an organic solvent and sonicate until completely dissolved to obtain a metal salt solution; (2) Dissolve 2-methylimidazole in an organic solvent and sonicate until completely dissolved to obtain a ligand solution; (3) The ligand solution described in step (2) is added dropwise into the metal salt solution described in step (1) and heated to react. After the reaction is completed, the precipitate is collected by centrifugation and washing to obtain the bimetallic MnCo-ZIF nanozyme.

[0010] Further, the cobalt salt in step (1) is cobalt nitrate hexahydrate, the manganese salt is manganese chloride tetrahydrate, the molar ratio of cobalt salt to manganese salt is (2:3)~(3:2), the molar ratio of 2-methylimidazole to the total molar amount of metal salt in step (2) is 3:1; the organic solvent in steps (1) and (2) is methanol.

[0011] Furthermore, in step (3), the heating reaction temperature is 110 ℃~130 ℃, and the reaction time is 3 h~5 h.

[0012] Further, in step (3), the collected precipitate is dried at a temperature of 50 ℃ to 70 ℃ for a time of 5 h to 7 h.

[0013] In a second aspect, the present invention provides an application of bimetallic MnCo-ZIF nanozymes in nitrite detection.

[0014] Furthermore, the application of a bimetallic MnCo-ZIF nanozyme in nitrite detection includes the following steps: Bimetallic MnCo-ZIF nanozymes and TMB were mixed thoroughly in an acetate-sodium acetate buffer solution, and nitrite solution was added. The reaction was carried out for 25-30 minutes, and the absorbance at 445 nm and 652 nm was measured. A 445 / A 652 Quantitative detection of nitrite concentration.

[0015] Furthermore, the application of bimetallic MnCo-ZIF nanozymes in nitrite detection is characterized by further comprising: Bimetallic MnCo-ZIF nanozymes were loaded onto filter paper to prepare test strips. During testing, nitrite solution, TMB solution, and acetate-sodium acetate buffer solution were added to the test strip in sequence. The nitrite was qualitatively or quantitatively detected by the color change of the test strip.

[0016] Furthermore, the quantitative detection involves performing RGB analysis on the test strip color to establish a linear relationship between the R / G value, R / B value, or G / B value and the nitrite concentration, thereby quantitatively detecting nitrite.

[0017] Furthermore, the linear detection range of the test strip for nitrite is 0~200 μM.

[0018] Furthermore, the concentration of the bimetallic MnCo-ZIF nanozyme is 80~100 μg / mL; the concentration of the TMB solution is 1~3 mmol / L; and the pH of the acetate-sodium acetate buffer solution is 4~5.

[0019] The beneficial effects of the technical solution provided by this invention are: (1) This invention prepares MnCo-ZIF via a simple solvothermal method. The preparation method is simple, the material is readily available, and the prepared MnCo-ZIF nanozyme exhibits good water dispersibility and stability, demonstrating good oxidase-like activity. This invention can catalyze the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) to generate a blue oxidation product with a distinct absorption peak at 652 nm. OX TMB). Under acidic conditions, nitrite can react with... OX TMB undergoes diazotization and oxidation reactions, resulting in a decrease in absorbance at 652 nm and an increase in absorbance at 445 nm. The solution color changes from blue to green and then to yellow. Using A... 445 / A 652 The change in the ratio enabled the quantitative detection of nitrite.

[0020] (2) By combining with smartphones, the color information of the reaction system is collected by a smartphone application and converted into RGB values. A portable detection platform for visualization and quantitative analysis of nitrite is constructed. A test strip sensor for visual detection of nitrite is developed to realize quantitative analysis and visual detection of nitrite in food. Attached Figure Description

[0021] Figure 1 This is a schematic diagram illustrating the preparation method and application process of the MnCo-ZIF nanozyme in Example 1; Figure 2 This is a transmission electron microscope (TEM) image of the MnCo-ZIF nanozyme in Example 1; Figure 3 This is a scanning electron microscope (SEM) image of the MnCo-ZIF nanozyme in Example 1; Figure 4 The Fourier transform infrared (FT-IR) spectrum of the MnCo-ZIF nanozyme in Example 1 is shown below. Figure 5 The image shows the X-ray diffraction (XRD) pattern of the MnCo-ZIF nanozyme in Example 1. Figure 6 The image shows the X-ray photoelectron spectrum of the MnCo-ZIF nanozyme in Example 1. Figure 7 The X-ray photoelectron spectrum of Co 2p of the MnCo-ZIF nanozyme in Example 1 is shown. Figure 8 The image shows the Mn 2p X-ray photoelectron spectrum of the MnCo-ZIF nanozyme in Example 1. Figure 9 The X-ray photoelectron spectrum of the MnCo-ZIF nanozyme in Example 1 is shown below. Figure 10 The absorbance (A) of the MnCo-ZIF nanozyme solution in Example 1 after 30 days of storage at room temperature. 445 / A 652 ( ) ratio diagram; Figure 11 This is a comparison of the UV spectra of the MnCo-ZIF nanozyme before and after the addition of TMB in Example 2; Figure 12 The Michaelis-Menten equation and double reciprocal plots are shown for the MnCo-ZIF nanozyme at different TMB concentrations in Example 2. Figure 13 The UV absorption spectra of the MnCo-ZIF nanozyme + TMB system in Example 2 under different gaseous environments; Figure 14The oxidase-like activity of the MnCo-ZIF nanozyme + TMB system in Example 2 in the presence of different scavengers; Figure 15 To detect the presence of O2• in the MnCo-ZIF+TMB nanozyme system in Example 2 - ESR spectra; Figure 16 The bar chart shows the TMB concentration optimization of the MnCo-ZIF nanozyme in Example 2; Figure 17 A bar chart showing the pH optimization of the MnCo-ZIF nanozyme in Example 2; Figure 18 The concentration optimization curve of MnCo-ZIF nanozyme in Example 2; Figure 19 The optimized incubation time curve for the MnCo-ZIF nanozyme in Example 2; Figure 20 This is a comparison of the UV spectra of the MnCo-ZIF nanozyme + TMB system before and after the addition of sodium nitrite in Example 3; Figure 21 The graph shows the ratio of UV absorbance of MnCo-ZIF nanozymes for different ions in Example 3, where the concentration of all metal ions is 100 μM. Figure 22 Example 3 shows the absorbance response curve to sodium nitrite concentration when MnCo-ZIF nanozyme is applied to sodium nitrite detection. Figure 23 The absorbance (A) in Example 3 445 / A 652 Linear relationship between A and sodium nitrite concentration; where A 445 and A 652 These are the absorbances of MnCo-ZIF at 445 nm and 652 nm, respectively. Figure 24 The image shows the color change of test strips based on different concentrations of sodium nitrite under sunlight in Example 4 for the MnCo-ZIF nanozyme sensor. Figure 25 This is a linear relationship graph between the sodium nitrite concentration and the R / G, R / B, and G / B values ​​of the test strip in Example 4. Detailed Implementation

[0022] The specific embodiments of the present invention are described in detail below. These embodiments are intended to more fully demonstrate the technical content of the present invention and help to understand the specific implementation process of the present invention, but their content should not be construed as limiting the scope of the claims of the present invention in any way. For those skilled in the art, various adjustments, modifications, and substitutions made to the embodiments without departing from the spirit and scope of the present invention are all within the scope of protection sought by the present invention.

[0023] Example 1 Preparation of MnCo-ZIF nanozymes ( Figure 1 ): (1) At room temperature, 0.582 g cobalt nitrate hexahydrate (0.002 mol) and 0.5936 g manganese chloride tetrahydrate (0.003 mol) solid powder were dissolved in 30 mL methanol solution and sonicated for 5 min until completely dissolved; (2) Dissolve 1.2316 g of 2-methylimidazole (0.015 mol) in 30 mL of methanol solution and sonicate for 5 min until completely dissolved; (3) Under continuous stirring, the solution obtained in step (2) was added dropwise to the solution obtained in step (1) to obtain a homogeneous mixed solution. Subsequently, the mixed solution was transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and reacted at 120°C for 4 h. After the reaction was completed, the precipitate was collected by centrifugation and washing. The precipitate was dried at 60°C for 6 h to obtain MnCo-ZIF nanozyme.

[0024] Material characterization of MnCo-ZIF nanozymes: (1) Morphological characteristics The morphology of MnCo-ZIF nanozymes was observed using TEM and SEM. Figure 2 Medium TEM images show that the prepared MnCo-ZIF nanozymes exhibit an irregular morphology; Figure 3 The SEM images clearly show that the MnCo-ZIF nanozyme has a distinct porous aggregated structure with an average diameter of approximately 100 nm.

[0025] (2) FT-IR analysis The chemical structure of MnCo-ZIF nanozymes was characterized by FT-IR, such as... Figure 4 As shown, in the FT-IR spectrum, 3440 cm⁻¹ - The peak at ¹ is attributed to the stretching vibration of O-H, 1630 cm⁻¹ - The characteristic peak at ¹ is attributed to the stretching vibration of C=C, 620 cm⁻¹ - ¹ and 528 cm - The peak at ¹ is related to the Mn-O stretching vibration.

[0026] (3) XRD analysis The crystal structure of MnCo-ZIF nanozymes was characterized by XRD, such as... Figure 5 As shown, the XRD pattern contains characteristic diffraction peaks belonging to both Co-ZIF nanozymes and Mn-ZIF nanozymes, indicating that the bimetallic ZIF material was successfully synthesized.

[0027] (4) XPS analysis XPS was used to analyze the elemental composition and chemical state of MnCo-ZIF nanozymes. Figures 6-9 As shown, the XPS full spectrum indicates the presence of five elements: C, N, O, Mn, and Co in the material. In the high-resolution XPS spectrum of Co 2p, the peaks at 795.8 eV and 780.4 eV belong to Co 2p1 / 2 and Co 2p3 / 2, respectively. The Co 2p1 / 2 peak can be further split into two peaks at 795.5 eV and 797.1 eV, and the Co 2p3 / 2 peak can be further split into two peaks at 780.2 eV and 781.8 eV, corresponding to Co³⁺ and Co³⁺, respectively. + and Co² + In the high-resolution XPS spectrum of Mn 2p, the peaks at 653.7 eV and 642.3 eV correspond to Mn 2p1 / 2 and Mn 2p3 / 2, respectively, and can be further decomposed into three peaks at 652.2, 653.5, 654.8 eV and 640.9, 642.6, 644.6 eV, respectively, corresponding to Mn² + Mn³ + and Mn 4+ Related. In the O 1s high-resolution XPS spectrum, 529.6 eV and 531.2 eV are attributed to lattice oxygen (O₂). L ) and surface-adsorbed oxygen (O A ).

[0028] (5) Stability test Figure 10 The absorbance (A) of the MnCo-ZIF nanozyme solution after 30 days of storage at room temperature. 445 / A 652 The ratio of MnCo-ZIF nanozymes to ZIF nanozymes is shown in the figure. The stability of the material was evaluated over a period of one month, with activity measured every 5 days. The results showed that the MnCo-ZIF nanozymes maintained high stability during the test.

[0029] Example 2 Preparation of Co-ZIF nanozymes: Compared with Example 1, step (1) was to dissolve 1.455 g of cobalt nitrate hexahydrate (0.005 mol) solid powder in 30 mL of methanol solution at room temperature and sonicate for 5 min until completely dissolved. The remaining steps were the same as in Example 1.

[0030] Preparation of Mn-ZIF nanozymes: Compared with Example 1, step (1) was to dissolve 0.9893 g of manganese chloride tetrahydrate (0.005 mol) solid powder in 30 mL of methanol solution at room temperature and sonicate for 5 min until completely dissolved. The remaining steps were the same as in Example 1.

[0031] To evaluate the oxidase-like activity of MnCo-ZIF nanozymes, TMB was used as the chromogenic substrate. A reaction system was prepared by mixing 100 µL MnCo-ZIF nanozyme solution (100 µg / mL), 100 µL TMB solution (3 mM), and 1800 µL HAc-NaAc buffer (pH 4.0, 50 mM), and the absorbance of the mixture was measured after 5 minutes of reaction. The absorbance of Co-ZIF nanozymes and Mn-ZIF nanozymes after the addition of TMB was measured using the same method and compared with that of MnCo-ZIF.

[0032] Figure 11 The image shows a comparison of the UV spectra of MnCo-ZIF nanozymes before and after the addition of 3,3',5,5'-tetramethylbenzidine (TMB). As can be seen from the image, MnCo-ZIF nanozymes have good oxidase activity, which is 14 times that of Co-ZIF nanozymes and 1.2 times that of Mn-ZIF nanozymes, respectively.

[0033] Figure 12 This is a Michaelis-Menten equation plot and a double reciprocal plot of MnCo-ZIF nanozymes at different TMB concentrations. The Michaelis-Menten constant (Km) of MnCo-ZIF nanozymes with respect to TMB was calculated. m The concentration was 0.087 mmol / L, and the maximum reaction rate (VL) was 0.087 mmol / L. max The K0 was 10.56 μM / min. The lower K0 m The value indicates that the nanozyme has a high affinity for the substrate, and the higher V value... max A value of 0 indicates a faster catalytic reaction rate.

[0034] Figure 13 The UV absorption spectra of the MnCo-ZIF nanozyme + TMB system under different gaseous environments show that dissolved oxygen plays a key role in the TMB oxidation reaction.

[0035] Figure 14The MnCo-ZIF nanozyme + TMB system exhibits oxidase-like activity in the presence of different free radical scavengers. PBQ can eliminate O2• present in the system. - IPA can eliminate •OH present in the system, and Trp can eliminate •OH present in the system. 1 O2. As shown in the figure, the absorbance of the system at 652 nm decreased significantly after the addition of PBQ, while the effects of IPA and Trp were relatively small, indicating that O2• - It is the main active species involved in the oxidation of TMB.

[0036] Figure 15 It is used to detect the presence of O2• in the MnCo-ZIF nanozyme + TMB system. - The ESR spectrum further confirmed the presence of O2• during the catalytic process. - The generation of .

[0037] Figure 16 To optimize the oxidase-like activity of MnCo-ZIF nanozymes, the effect of TMB concentration was systematically investigated. The optimal TMB concentration was determined to be 0.15 mM.

[0038] Figure 17 To optimize the oxidase-like activity of MnCo-ZIF nanozymes, the effect of solution pH was systematically investigated. The optimal pH was determined to be 4.

[0039] Figure 18 To optimize the oxidase-like activity of MnCo-ZIF nanozymes, the effect of material concentration was systematically investigated. The optimal material concentration was determined to be 5 μg / mL.

[0040] Figure 19 To optimize the oxidase-like activity of MnCo-ZIF nanozymes, the effect of reaction time was systematically investigated. The optimal reaction time was determined to be 5 min.

[0041] Example 3 Detection of sodium nitrite by MnCo-ZIF nanozyme: Colorimetric detection of sodium nitrite was performed in 2 mL centrifuge tubes. First, 100 μL (100 μg / mL) of MnCo-ZIF nanozyme and 100 μL (3 mmol / L) of TMB were mixed thoroughly in 1700 μL of Hac-NaAc buffer solution. After reacting for 5 min, 100 μL of sodium nitrite solution of different concentrations was added, and the reaction was continued at room temperature for 30 min. The absorption spectra were then measured in the wavelength range of 350–800 nm. The absorbance ratio (Ag) at 445 nm to 652 nm was analyzed. 445 / A 652 )Quantitative detection of sodium nitrite was performed.

[0042] Figure 20 The figure shows a comparison of the UV spectra of the MnCo-ZIF nanozyme + TMB system before and after the addition of sodium nitrite under optimal reaction conditions (TMB concentration 0.15 mM, pH 4, material concentration 5 μg / mL, reaction time 5 min). After the addition of sodium nitrite, the UV-Vis absorption spectrum changed significantly, as shown in the figure. A new absorption peak appeared at 445 nm, while the absorption intensity at 652 nm decreased significantly.

[0043] Figure 21 This is a graph showing the ratio of UV absorbance of MnCo-ZIF nanozymes to different ions, where the concentration of each metal ion is 100 μM. As shown in the figure, the MnCo-ZIF nanozyme has a significant response to sodium nitrite, but a lower response to other ions. Therefore, this nanozyme can specifically detect sodium nitrite.

[0044] Figure 22-23 These are the response curves and linear curves of the MnCo-ZIF nanozyme of this invention to sodium nitrite in the concentration range of 0-200 μM. For example... Figure 22 As shown, under optimal conditions, the quantitative detection of sodium nitrite showed that with increasing sodium nitrite concentration, the absorbance of the MnCo-ZIF nanozyme at 445 nm gradually increased, while the absorbance at 652 nm gradually decreased. Correspondingly, the absorbance ratio A... 445 / A 652 The value gradually increases with increasing sodium nitrite concentration, indicating that the method of quantitatively detecting sodium nitrite by ratio colorimetric detection is feasible. Figure 23 Sodium nitrite concentration and A 445 / A 652 The linear curve (ratio of absorbance at 445 nm to 652 nm) shows that the nanozyme exhibits good linearity for sodium nitrite, with a linear range of 0 to 200 μM. This confirms the reliability of the nanozyme in the quantitative detection of sodium nitrite. The catalytic mechanism of MnCo-ZIF for TMB oxidation is that, under the influence of oxygen vacancies on the MnCo-ZIF surface, O2 can be effectively converted by low-valence Co and Mn ions (Co... 2+ Mn 2+ and Mn 3+ It accepts electrons and is activated to become O2• - The generated O2• - Subsequently, TMB molecules were oxidized to blue on the MnCo-ZIF surface. OX TMB. Next, Mn 2+ and Mn 3+ Co 3+ Restore to Co 2+ This is due to Co 3+ / Co2+ The standard reduction potential (E0 = 1.81 V) is higher than that of Mn. 3+ / Mn 2+ (E0=1.51 V) and Mn 4+ / Mn 3+ This is due to (E0 = 0.15 V). Meanwhile, Mn 4+ and Mn 3+ They are reduced to Mn by accepting electrons from the adsorbed TMB. 3+ and Mn 2+ .

[0045] Example 4 Filter paper was cut into uniformly sized test strips, which were then immersed in a dispersion of MnCo-ZIF nanozyme at a concentration of 100 μg / mL and dried in an oven. Subsequently, 30 μL of NO2 at different concentrations was added. - The solution was dried in air, and 30 μL of a 1 mmol / L solution of 3,3',5,5'-tetramethylbenzidine (TMB) was added and dried in air. 20 μL of acetate-sodium acetate buffer solution (pH 4.0) was added to start the reaction.

[0046] Figure 24 This is a photograph showing the color change of the test strip of the MnCo-ZIF nanozyme sensor prepared in this invention under sunlight as the concentration of sodium nitrite increases.

[0047] Figure 25 RGB analysis of the test strip color under sunlight using the ColorMax application revealed a good linear relationship between R / G, R / B, and G / B values ​​and sodium nitrite concentration (0-180 μM). This indicates that the test strip prepared using ratiometric colorimetric nanozymes with a bimetallic strategy can be successfully coupled with a smartphone platform, transforming traditional colorimetric detection into portable, real-time analysis and significantly improving detection efficiency.

[0048] Example 5 To verify the practicality of this method, sodium nitrite was spiked and recovered from actual samples (tap water, sausage, pickled vegetables, and tea eggs). 100 μL (100 μg / mL) of MnCo-ZIF nanozyme and 100 μL (3 mmol / L) of TMB were mixed thoroughly in 1700 μL of actual sample solution. After reacting for 5 min, 100 μL of sodium nitrite solutions of different concentrations (final concentrations of 10 μM, 50 μM, and 100 μM) were added, and the reaction was continued at room temperature for 30 min. The absorption spectra were then measured in the wavelength range of 350-800 nm. The absorbance ratio (Ag) at 445 nm to 652 nm was analyzed. 445 / A652 The recovery rate of sodium nitrite was calculated by substituting the values ​​into the linear regression curve equation. Tap water from the campus water supply was collected and filtered directly through a 0.22 μm membrane before testing. The specific pretreatment steps for samples such as ham were as follows: (1) Take 5 grams of chopped ham, put it into a 100 mL conical flask, add 50 mL of water, and extract with ultrasound for 30 minutes to ensure full dispersion.

[0049] (2) Heat the mixture in a 75 °C water bath for 5 minutes, cool to room temperature, quantitatively transfer to a 100 mL volumetric flask, dilute to the mark, mix thoroughly, and then filter.

[0050] (3) Centrifuge at 10,000 rpm for 5 minutes, collect the supernatant, filter it through a 0.22 μm membrane and use it for analysis.

[0051] Table 1 shows the recovery rates of sodium nitrite in actual samples. The recoveries, measured using a colorimetric spectrophotometer in tap water, sausage, pickled vegetables, and tea eggs, ranged from 96.7% to 106.7%. The recoveries measured using a smartphone sensing platform ranged from 98% to 104%, while the recoveries measured using a test strip sensing platform ranged from 98.5% to 106.4%. This indicates that the MnCo-ZIF nanozyme has the potential to achieve quantitative detection of sodium nitrite in actual samples.

[0052] Table 1 Recovery rate of sodium nitrite in actual samples The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a bimetallic MnCo-ZIF nanozyme, characterized in that, The preparation method comprises the following steps: (1) Dissolve cobalt salt and manganese salt in an organic solvent and sonicate until completely dissolved to obtain a metal salt solution; (2) Dissolve 2-methylimidazole in an organic solvent and sonicate until completely dissolved to obtain a ligand solution; (3) The ligand solution described in step (2) is added dropwise into the metal salt solution described in step (1) and heated to react. After the reaction is completed, the precipitate is collected by centrifugation and washing to obtain the bimetallic MnCo-ZIF nanozyme.

2. The method for preparing bimetallic MnCo-ZIF nanozymes according to claim 1, characterized in that, The cobalt salt mentioned in step (1) is cobalt nitrate hexahydrate, the manganese salt is manganese chloride tetrahydrate, the molar ratio of cobalt salt to manganese salt is (2:3)~(3:2), the molar ratio of 2-methylimidazole to the total molar amount of metal salt in step (2) is 3:1; the organic solvent mentioned in steps (1) and (2) is methanol.

3. The method for preparing bimetallic MnCo-ZIF nanozymes according to claim 1, characterized in that, In step (3), the heating reaction temperature is 110 ℃~130 ℃ and the reaction time is 3 h~5 h.

4. The method for preparing bimetallic MnCo-ZIF nanozymes according to claim 1, characterized in that, In step (3), the collected precipitate is dried at a temperature of 50 ℃ to 70 ℃ for a time of 5 h to 7 h.

5. The application of a bimetallic MnCo-ZIF nanozyme prepared by any one of the preparation methods described in claims 1 to 4 in the detection of nitrite.

6. The application of the bimetallic MnCo-ZIF nanozyme according to claim 5 in nitrite detection, characterized in that, Includes the following steps: Bimetallic MnCo-ZIF nanozymes and TMB were mixed thoroughly in an acetate-sodium acetate buffer solution, and nitrite solution was added. The reaction was carried out for 25-35 minutes, and the absorbance at 445 nm and 652 nm was measured. A 445 / A 652 Quantitative detection of nitrite concentration.

7. The application of the bimetallic MnCo-ZIF nanozyme according to claim 5 in nitrite detection, characterized in that, Also includes: Bimetallic MnCo-ZIF nanozymes were loaded onto filter paper to prepare test strips. During testing, nitrite solution, TMB solution, and acetate-sodium acetate buffer solution were added to the test strip in sequence. The nitrite was qualitatively or quantitatively detected by the color change of the test strip.

8. The application of the bimetallic MnCo-ZIF nanozyme according to claim 7 in nitrite detection, characterized in that, The quantitative detection method involves performing RGB analysis on the test strip color and establishing a linear relationship between the R / G value, R / B value, or G / B value and the nitrite concentration to quantitatively detect nitrite.

9. The application of the bimetallic MnCo-ZIF nanozyme according to claim 8 in nitrite detection, characterized in that, The linear detection range of the test strip for nitrite is 0~200 μM.

10. The application of the bimetallic MnCo-ZIF nanozyme according to claim 6 or 7 in nitrite detection, characterized in that, The concentration of the bimetallic MnCo-ZIF nanozyme is 80~100 μg / mL; the concentration of the TMB solution is 1~3 mmol / L; and the pH of the acetate-sodium acetate buffer solution is 4~5.